PENGARUH KINERJA BAURAN PEMASARAN TERHADAP DAYA SAING USAHA KECIL SEKTOR INDUSTRI KOPI BUBUK DI PROPINSI LAMPUNG - Bangsawan, Satria (Indonesian Journal of Socio Economics)
Program to improve performance of small industries of ground coffee processing intends to empower their competitive advantage.  It ultimate aim is at increasing revenues from agricultural export for the province. The objective of the study is to analyze the effect of small business marketing mix in improving competitive advantage of the company.  The study employs survey method involving 38 small scale ground coffee industries in Lampung Province.  A survey method with marketing management science approach has been applied. Observation was carried out on small business of ground coffee in Lampung with 38 respondent sample sizes as owner/manager of the company. Data collection was carried out with interview technique using questioner to the selected respondent, using cluster random sampling method. Path analysis has been applied to analyze the collected data.  The study shows that the competitive Advantage of ground coffee small business was affected by the performance of marketing mix appeared to be combination of product, price, promotion, and distribution.